Skyrmions in the Moore-Read state at nu=5/2. - Wójs, A; Möller, G; Simon, S; Cooper, N (2010)
We study charged excitations of the non-Abelian Moore-Read liquid at a filling factor nu=5/2, allowing for spin depolarization. Using a combination of numerical studies, and taking account of nonzero well widths, we find that at a sufficiently low Zeeman energy it is energetically favorable for charge e/4 quasiholes to bind into Skyrmions of charge e/2. We show that Skyrmion formation is further promoted by disorder, and argue that this can lead to a depolarized nu=5/2 ground state in realistic experimental situations. We comment on the consequences for the activated transport.